Innovations in verb accommodations in Dorota Masłowska’s Wojna polsko-ruska pod flagą biało-czerwoną and their translation into Russian - Orzechowska, Joanna (Papers in Linguistics, 2020)
The article presents changes in syntactic accommodation in a novel by Dorota Masłowska.